2007
DOI: 10.1177/0038038507082314
|View full text |Cite
|
Sign up to set email alerts
|

`A Darker Shade of Pale?' Whiteness, the Middle Classes and Multi-Ethnic Inner City Schooling

Abstract: Drawing on data from interviews with 63 London-based families, this article argues that there are difficult and uncomfortable issues around whiteness in multi-ethnic contexts. Even those parents, such as the ones in our sample, who actively choose ethnically diverse comprehensive schools appear to remain trapped in white privilege despite their political and moral sentiments. This is a complicated question of value; of having value, finding value in, getting value from, and adding value. Even those white middl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
238
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 245 publications
(245 citation statements)
references
References 31 publications
4
238
2
1
Order By: Relevance
“…The qualitative research has therefore focussed on the types of resources parents have, such as the time and economic cost involved in choosing a school other than a local one or the ways in which some parents prioritise criteria such as school ethos above academic reputation (Reay et al, 2007). In explaining this situation many authors have found Bourdieu"s relational concepts of capital, habitus and field useful and we now go on to explain why these concepts are central to the framework for this study.…”
Section: Choice and The Market: Working With Bourdieumentioning
confidence: 99%
“…The qualitative research has therefore focussed on the types of resources parents have, such as the time and economic cost involved in choosing a school other than a local one or the ways in which some parents prioritise criteria such as school ethos above academic reputation (Reay et al, 2007). In explaining this situation many authors have found Bourdieu"s relational concepts of capital, habitus and field useful and we now go on to explain why these concepts are central to the framework for this study.…”
Section: Choice and The Market: Working With Bourdieumentioning
confidence: 99%
“…From this vantage point, the relationship between those who do the embracing and those who are embraced is dependent on the selfperceived altruism or generosity of the 'host' (our perception that minority groups are indeed worthy of our generosity), and a corresponding supplication of minorities (Burchell 2001). This logic is premised on a partial or conditional acceptance (so long as they have something to offer us) which also produces unacceptable 'others' who have nothing to offer (Reay et al 2007). The power relationship implied in the logic of interculturalism, therefore, is such that those who are not seen to be making a contribution are implicitly positioned as being undeserving of this self-perceived generosity.…”
Section: Intercultural Education As Symbolic Violencementioning
confidence: 99%
“…The power relationship implied in the logic of interculturalism, therefore, is such that those who are not seen to be making a contribution are implicitly positioned as being undeserving of this self-perceived generosity. From this perspective, the embracing of an acceptable ethnic 'other' via interculturalism is, in effect, an 'excluding inclusivity' (Reay et al 2007(Reay et al , 1054) which fails to disrupt, yet brilliantly disguises, power relationships between majoritised and minoritised groups in society.…”
Section: Intercultural Education As Symbolic Violencementioning
confidence: 99%
See 2 more Smart Citations